2012
DOI: 10.1128/aem.06251-11
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Transcriptional Profiles and Phenotypes Exhibited by Escherichia coli O157:H7 Isolates Related to the 2006 Spinach-Associated Outbreak

Abstract: In 2006, a large outbreak of Escherichia coli O157:H7 was linked to the consumption of ready-to-eat bagged baby spinach in the United States. The likely sources of preharvest spinach contamination were soil and water that became contaminated via cattle or feral pigs in the proximity of the spinach fields. In this study, we compared the transcriptional profiles of 12 E. coli O157:H7 isolates that possess the same two-enzyme pulsed-field gel electrophoresis (PFGE) profile and are related temporally or geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…For instance, outbreaks of Salmonella Typhimurium and Escherichia coli O157:H7 in Europe and USA were linked to leafy vegetables such as lettuce and spinach (Horby et al, 2003;Heaton and Jones, 2008;Parker et al, 2012). Epidemic survey also showed a high possibility of leafy vegetables infected with E. coli O157:H7 at the farm (Parker et al, 2012;Cooley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, outbreaks of Salmonella Typhimurium and Escherichia coli O157:H7 in Europe and USA were linked to leafy vegetables such as lettuce and spinach (Horby et al, 2003;Heaton and Jones, 2008;Parker et al, 2012). Epidemic survey also showed a high possibility of leafy vegetables infected with E. coli O157:H7 at the farm (Parker et al, 2012;Cooley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemic survey also showed a high possibility of leafy vegetables infected with E. coli O157:H7 at the farm (Parker et al, 2012;Cooley et al, 2007). In particular, Parker et al (2012) reported that a large outbreak of E. coli O157:H7 in 2006 was linked to the consumption of ready-to-eat baby spinach, likely contaminated by soil and water. From those reports, it is considered that the cultivation period is a critical point in preventing contamination with pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, in fragmented agricultural and forest landscapes, wildlife can contribute a large portion of the fecal pollution (8)(9)(10)(11), also serving as a reservoir for pathogens. E. coli O157:H7 was found in feral swine in Sweden (12) and in California, USA (13)(14)(15); E. coli O157:H7 were also isolated from feces of white-tailed deer cograzing with cattle (16)(17)(18). Black-tailed deer were identified as a source of E. coli O157:H7 strawberry-transmitted infection in Oregon, which caused 15 illness cases, including two deaths (19).…”
mentioning
confidence: 99%
“…RNA extraction, cDNA labeling, and microarray hybridization were performed as described previously with slight modifications (37,50). Briefly, total RNA was extracted using the Promega SV total RNA kit, with additions of 3 mg ml Ϫ1 of lysozyme (Fisherbrand) to a bacterial cell suspension.…”
mentioning
confidence: 99%